Global Sport Power Europe? The Efficacy of the European Union in Global Sport Regulation*. (29th November 2016) - García, Borja; Meier, Henk Erik
Abstract: The effectiveness of the European Union (EU) as global regulator is controversial. Some scholars characterize the EU as one of the most important shapers of global regulations; others argue that the EU's effectiveness critically depends on its regulatory cohesion, the political opportunity structure and regulatory capacity of its interlocutors. Since global sport represents a regionally segmented industry and is governed by private actors of diverse regulatory capacity, global sport regulation represents an excellent domain to study these propositions systematically. Comparative case studies on global sport regulation support the idea that the EU can impose its regulatory ambitions on sport governing due to market size and regulatory capacity. However, the broader political opportunity structure is found to be relevant and the EU does not appear as a strong regulator of global sports.